Моделювання деформованого стану східчастих пустотілих поковок в процесі розкочування - Косілов, Максим Сергійович; Марков, Олег Євгенович; Герасименко, Олексій Васильович; Шевцов, Сергій Олександрович (НТУ "ХПІ", 2017)
В роботі описані результати дослідження отримання східчастої поковки. Дослідження були проведені шляхом виконання експерименту на свинцевих моделях. Встановлено, що через різну товщину стінки виступу та уступу заготовки, ступінь деформації уступу більший ніж виступу. Через це утворюється конусна форма поковки. В залежності від відносного діаметру виступу напрям конусності заготовки змінюється. Зміна конусності відбувається в процесі одночасного деформування виступу та уступу, через більшу тангенціальну деформацію уступу.

This paper describes the results of a study to obtain step forgings. It is known that in order to provide greater safety and increase the life of the reactor unit, it is necessary to produce complex elements of the body, which combine several simple ones. The study the shape and deformation of stepped hollow forgings during rolling is the purpose of the work. The study was conducted by the experiment on the lead models. Adding 1% antimony to lead has allowed approximating the mechanical characteristics of the model material to the properties of steel 34HNM in hot condition. The research was conducted in a laboratory environment on a hydraulic press. During the gradual rolling of the flange and the flange with the ledge the difference between the total deformations for the ledge and the protuberance decreases when the rolling the ledge is started. The parameters of taper and total deformation are chosen for setting the shape change. Due to different thickness of the flange wall and the ledge wall of the workpiece, the strain degree of the ledge is greater than the flange is established. This also leads to large total deformations in the workpiece. Consequently, a conical form of forging is formed by enlarging. Depending on the relative diameter of the flange, taper direction of the workpiece changes. Changing the taper occurs while simultaneously deforming the flange and the ledge due to a large tangential deformation of the ledge.
Modeling of the deformed state of stepped hollow forgings in the process of enlarging
Keywords: східчаста поковка; тангенціальна деформація; конусність; бойок; розкочування; обтискання; forging; deformation; taper; die; enlarging; step forging; reduction